Die Aktualisierungspflicht beim Kauf von Waren mit digitalen Elementen: Eine dogmatisch-systematische Einordnung in das Kauf- und Gewährleistungsrecht - Manhardt, Tobias (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Digitization is advancing. More and more products contain software, are interconnected, and cannot fulfill their functions without digital elements. The implementation of the Sale of Goods Directive introduced an obligation to update goods with digital elements in consumer sales law (§ 475b BGB). It expands the sales contract with elements of a continuing obligation. The obligation to update is a primary obligation of the seller to maintain conformity even after delivery. However, the "right to updates" of the buyer can only be enforced indirectly through the secondary remedies. When interpreting and applying the remedies of § 439 BGB, special considerations must be taken into account.